THE ROLE OF MARKETING IN THE DEVELOPMENT OF SERVICE ENTERPRISES - Nabiyeva Nilufar Muratovna (Journals Park Publishing, 2022)
Accelerating changes in the environment, the emergence of new requests and changing the position of the consumer, the emergence of new unexpected business opportunities, the development of information networks, the rapid dissemination of information, changing the role of human resources and a number of other reasons have led to a sharp increase in the value of alternative analysis and strategy selection. The current situation in the market and the growth of enterprises specializing in services have forced a new look at the principles of forming a marketing strategy. It follows that traditional methods of shaping and selecting alternatives in strategic planning need to be modified and adapted to specific conditions.
Keywords: Marketing Strategy; Services Marketing; Ansoff Matrix